Supplier Relationship Management Practices and Firm Performance: Evidence from Small and Medium Enterprises in India - Joshi, Swati (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the supplier relationship management practices and firm performance: evidence from small and medium enterprises in India. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on Supplier Relationship Management (SRM) in Indian SMEs reveals a positive link between effective SRM practices and firm performance. It highlights benefits such as improved operational efficiency, cost reduction, and enhanced product quality. However, challenges like resource constraints hinder widespread adoption. Overall, prioritizing strong supplier relationships can boost SME competitiveness in India. Unique Contribution to Theory, Practice and Policy: Transaction cost economics (TCE), resource dependency theory (RDT) & social exchange theory (SET) may be used to anchor future studies on analyze the supplier relationship management practices and firm performance: evidence from small and medium enterprises in India. SMEs could also benefit from capacity-building initiatives aimed at enhancing their negotiation skills, contract management capabilities, and technological adoption to facilitate efficient SRM processes. Policymakers can leverage research findings to design supportive policies aimed at strengthening the SME ecosystem in India.